Rational Designs for Lithium‐Sulfur Batteries with Low Electrolyte/Sulfur Ratio - Guo, Junling; Pei, Huayu; Dou, Ying; Zhao, Siyuan; Shao, Guosheng; Liu, Jinping (Advanced functional materials, 2021)
Lithium‐sulfur batteries (LSBs) are considered a promising next‐generation energy storage device owing to their high theoretical energy density. However, their overall performance is limited by several critical issues such as lithium polysulfide (PS) shuttles, low sulfur utilization, and unstable Li metal anodes. Despite recent huge progress, the electrolyte/sulfur ratio (E/S) used is usually very high (≥20 µL mg−1), which greatly reduces the practical energy density of devices. To push forward LSBs from the lab to the industry, considerable attention is devoted to reducing E/S while ensuring the electrochemical performance. To date, however, few reviews have comprehensively elucidated the possible strategies to achieve that purpose. In this review, recent advances in low E/S cathodes and anodes based on the issues resulting from low E/S and the corresponding solutions are summarized. These will be beneficial for a systematic understanding of the rational design ideas and research trends of low E/S LSBs. In particular, three strategies are proposed for cathodes: preventing PS formation/aggregation to avoid inadequate dissolution, designing multifunctional macroporous networks to address incomplete infiltration, and utilizing an imprison strategy to relieve the adsorption dependence on specific surface area. Finally, the challenges and future prospects for low E/S LSBs are discussed. Emergent works aiming at low electrolyte/sulfur ratio (E/S) lithium‐sulfur batteries (LSBs) are summarized on the basis of specific issues resulting from the use of low E/S along with solutions to address these issues. Subsequently, the challenges of these strategies and the future prospects for LSBs with low E/S are discussed in this review.